Professional Premises - O'Connell, Andrew (2020)
An amateur theatre group is rehearsing Shakespeare’s The Tempest. Malcolm, the director, fancies himself as an expert on the play and on theatre in general. Dave, who has been cast to play Prospero, grows increasingly frustrated with Malcolm’s lack of direction and, as he sees it, lack of knowledge. Dave sets out to expose Malcolm as a fraud. Lindsay, who has been cast to play Miranda, sees no reason why Dave should be hostile to Malcolm, and sees less of a reason to expose him as a fraud, even if he is one. She tries to maintain a good working relationship with everyone. She calls out Dave for his lack of respect, his hypocrisy, pride, and is arrogance. But Dave won’t stop until he has laid bare Malcolm’s ignorance, which he does in brutal style. Malcolm ends up walking away from the production never, it seems, being able to bring himself to direct another play again.